Invitro Regeneration and Mass-Clonal Proliferation of Wheat through embryonic formation - Khaskheli, Allah Jurio; Ali, Muharam; Khaskheli, Muhammad Ibrahim; Memon, Zohra Fatima; Shah, Sayyed Zakir Hussain; Awan, Saleem; Magsi, Bilqees; Rajput, Ushba Jabeen; Khaskheli, Mohsin Ali (International Journal of Environment, Agriculture and Biotechnology, 2019)
The present study was conducted to determine the regeneration potential and producing mass-clonal production of wheat through embryogenesis. A total of 60 selected wheat seeds were surface sterilized and inoculated on different culture bottles under controlled condition. The seeds were emerged in MS basal media and later supplemented with different concentrations of BAP (Benzyl-amino purine) and IAA (Indole-acetic acid). The Observation on servile rate, regeneration capability, length of leaves, length regenerated seedlings, length and number roots were observed. Resultsfurther expressed that the media MS-MIII showed maximum length of leaves and roots of seedlings followed by cultured on media supplemented with 10µg/L or 20µg/L or 30µg/L each of IAA and BAP. Though, seedlings obtained under the concentration of 40µg/L of IAA and BAP were relatively similar and showed significantly moderate result followed by cultured on the medium supplemented with 30µg/L. furthermore, the rooted plants were then transplanted into the substrate and acclimatized in the laboratory greenhouse where humid cavity available. The acclimatization in the humid cavity showed optimistic effect on the number of survived plants.